Weight loss improves the adipogenic capacity of human preadipocytes and modulates their secretory profile - Rossmeislová, Lenka; Malisová, Lucia; Kracmerová, Jana; Tencerová, Michaela; Kovácová, Zuzana; Koc, Michal; Siklová-Vítková, Michaela; Viquerie, Nathalie; Langin, Dominique; Stich, Vladimír (Diabetes.., 2013)
Calorie restriction-induced weight loss is accompanied by profound changes in adipose tissue characteristics. To determine the effect of weight loss on differentiation of preadipocytes and secretory capacity of in vitro differentiated adipocytes, we established cultures of these cells from paired subcutaneous adipose tissue biopsies obtained before and at the end of weight-reducing dietary intervention (DI) in 23 obese women. Based on lipid accumulation and the expression of differentiation markers, in vitro adipogenesis increased after weight loss and it was accompanied by enhanced expression of genes involved in de novo lipogenesis. This effect of weight loss was not driven by changes of peroxisome proliferator-activated receptor γ sensitivity to rosiglitazone. Weight loss also enhanced the expression of adiponectin and leptin while reducing that of monocyte chemoattractant protein 1 and interleukin-8 by cultured adipocytes. Thus, the weight-reducing (DI) increased adipogenic capacity of preadipocytes and shifted their secretion toward lower inflammatory profile. Reprogramming of preadipocytes could represent an adaptation to weight loss leading to partial restoration of preobese adipose tissue traits and thus contribute to the improvement of metabolic status. However, enhanced adipogenesis could also contribute to the unwanted weight regain after initial weight loss.
Keywords: adipogeneze; obezita; hmotnostní úbytek; Humans; cytokiny; Female; Interleukin-8; ELISA; Adipogenesis; interleukin-8; lidé; Cells, Cultured; chemokin CCL2; Enzyme-Linked Immunosorbent Assay; Adipocytes; tukové buňky; ženské pohlaví; Leptin; Adiponectin; Chemokine CCL2; kultivované buňky; leptin; Thiazolidinediones; Cytokines; adiponektin; PPAR gama; rosiglitazon; Obesity; thiazolidindiony; Rosiglitazone; PPAR gamma; Weight Loss